Enhancing Udeng Pacul Gowang Craftmen’s Business Through Technology: A Community Service Initiative in Wonoayu, Pagerngumbuk, Sidoarjo - Januari Pratama Nurratri TR; G. Oka Warmana; Dewi Deniaty Sholihah (Future Science, 2023)
The Udeng craftsmen in Sidoarjo have traditionally adhered to rudimentary techniques and order-based marketing approaches to sustain their livelihoods. Conversely, in the contemporary digital era, the ubiquity of technology is undeniable. This academic paper elucidates the outcomes of a community service initiative aimed at elevating the udeng pacul gowang craftsmen in Wonoayu, Pagerngumbuk, Sidoarjo, by harnessing the potential of technology in their business endeavors. Furthermore, this community service comprises three principal activities, each firmly grounded in the corresponding theoretical framework of “pillars of a digital ecosystem for enterprises”. To commence, the community received training in the proficient management of digital-based financial record-keeping, facilitated through the utilization of an Android application known as